#TITLE_ALTERNATIVE# - MUHAMMAD AKBAR (NIM : 10212067), RIDHO
Relative permeability is the main and most important parameter to be estimated in a multiphase fluid flow analysis inside complex medium such as porous media. Estimating relative permeability curve is a challenging work since there is no exact solution in Navier-Stokes equation for complex multiphase flow. In this research, relative permeability is computed through simulation of multiphase fluid flow inside a porous media domain. Simulation is run under Lattice-Boltzmann Color Gradient algorithm, or better known as LBM-RK algorithm. We managed to develop the algorithm to be implemented both in 2D and 3D domain. Some validation in simple system has been conducted and the result is consistent with either experiment or analytical solution. Finally, LBM-RK is successfully implemented to simulate immiscible displacement flow inside porous media by non-wetting fluid to generate the relative permeability curve. We also vary some simulation parameter to study the dependence of permeability with capillary number, geometry complexity of porous media, and image size of the rock sample.